Penyebab Rendahnya Keikutsertaan Mahasiswa FIS Universitas Negeri Medan Dalam Penyampaian Aspirasi Kepada Pemerintah - Tengku Abdillah Azis; Derita Ramai Durubanua; Putri Roito Lumbantobing (International Forum of Researchers and Lecturers, 2024)
This research explores the low political participation of students in the Faculty of Social Sciences at the State University of Medan in conveying their aspirations to the government. Characteristics of a democratic country highlight the active involvement of its citizens in political activities, including student political participation. Student organizations are considered small entities similar to the government. The literature review involves definitions of democracy, forms of democracy, and political participation. The research method uses a quantitative and descriptive approach with data collection through questionnaires and interviews. The research findings indicate that the majority of students rarely or never convey their aspirations, driven by a lack of confidence that their aspirations will be responded to. Respondent profiles show a majority from the Geography department and with student registration numbers from the year 2022. Factors influencing low participation include lack of trust, low awareness, and lack of support from student organizations. Recommendations include increasing courage, organizational support, student awareness, interdisciplinary networks, innovation, easily accessible communication platforms, and active government engagement. This research provides in-depth insights and offers recommendations to enhance student participation in conveying political aspirations.